2013
DOI: 10.1007/s11748-013-0276-7
|View full text |Cite|
|
Sign up to set email alerts
|

Acute respiratory distress syndrome after pulmonary resection

Abstract: Postoperative acute respiratory distress syndrome (ARDS) is a recognized complication of pulmonary resection. It is characterized by the acute onset of hypoxemia with radiographic infiltrates consistent with pulmonary edema, without elevations in the pulmonary capillary wedge pressure. Many studies suggest that around 2-5 % of patients develop some degree of lung injury, and the mortality from ARDS following pulmonary resection remains high. ARDS following thoracotomy and lung resection has a miserable prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 90 publications
0
24
1
1
Order By: Relevance
“…Twenty patients (69.0%) received VV ECLS. Even though ECLS support was applied, the mortality rate of our patients was higher (75.9%) than that in previous reports [6,11]. This finding was due to the relative severity of disease in the patients in our study.…”
Section: Commentcontrasting
confidence: 69%
See 2 more Smart Citations
“…Twenty patients (69.0%) received VV ECLS. Even though ECLS support was applied, the mortality rate of our patients was higher (75.9%) than that in previous reports [6,11]. This finding was due to the relative severity of disease in the patients in our study.…”
Section: Commentcontrasting
confidence: 69%
“…The mortality of patients with severe ARDS with conventional therapy was reported to be 50% to 70% 2 decades ago, but has declined as time has passed [5,16,17]. A recent multicenter study revealed a 28-day mortality level of approximately 35% [18]; and ARDS after pulmonary resection exhibited a poor prognosis, with mortality ranging from 25% to 100% [6][7][8][9][10]. Cardiovascular complications including myocardial infarction, pulmonary embolism, atrial fibrillation, right ventricular dysfunction, and postoperative pulmonary hypertension can occur in as many as 30% of patients after general thoracic surgery.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a phase II study (WJOG 6711L) has been developed to validate effectiveness and the safety of perioperative administration of PFD to lung cancer patients with IPF, trying to analyse whether PFD reduces lung injury after lung resection 21 .…”
Section: Effect Of Pirfenidone In Ipfmentioning
confidence: 99%
“…Immediately following pulmonary resection, several conditions are known to enhance extravascular lung water (EVLW) expansion including fluid infusion in the intraoperative period. EVLW expansion can generate the impairment of gas exchanges that can lead to postoperative acute lung injury which is associated to mortality ranging from 20% up to 100% (21). Therefore, in our program, we suggest avoiding fluid overload, keeping fluid administration to a minimum and monitoring hydric balance with urinary drainage catheters positioned in the operating room.…”
Section: Fluid Controlmentioning
confidence: 99%